ENDOCRINE PANCREATIC FUNCTION IN ACUTE PANCREATITIS - P. V. Novokhatny (Zaporožskij Medicinskij Žurnal)
Introduction Among the organs of internal secretion pancreas has a special place thanks to active exocrine function and a wide range of physiological actions of produced hormones. Violations of endocrine pancreas arises in 6.5-38 % of patients with acute pancreatitis. However, there is still no clear understanding of the pathogenetic mechanisms of hormonal dysfunction of the pancreas in acute pancreatitis, there is no uniform algorithms for its correction.